(untitled) (Texas Journal of Medical Science, 2024)
Comparative assessment of the effect of calcium channel blockers amlodipine and lercanidipine on functional status of kidneys, intrarenal hemodynamics and vascular system remodeling in patients with stage III of chronic kidney disease